Narrativas de la ciudad bambuquera de américa: proyecto de aula desde la virtualidad (Memorias Sifored - Encuentros Educación UAN, 2021)
This writing presents the experience carried out through remote access at the Colom-bus American School educational institution with fourth grade students, in the development of the project entitled "Narratives of the Bambuquera City of America." Under the Teaching for Understanding (EPC) framework, students converged knowledge and know-how in their learning process.This experience highlights the importance of the student being the protagonist of the class; With this, autonomy, collaborative work, problem solving, decision-making, among others, are promoted. Likewise, the project was of an interdisciplinary nature in which the areas of Natural Sciences, Social Sciences, Spanish language, foreign languages and technology and information technology, which allowed students to get to know and analyze the city of Neiva from different dimensions.
Keywords: Teaching for understanding; Collaborative work; Interdisciplinarity; Knowing; Autonomy